The Indian megacity and economic reforms / A.K. Jain ; foreword by M.N. Buch. - Jain, A. K. (Ashok Kumar) (Management Pub. Co, 1996)
Summary: With reference to Bombay, Calcutta, Delhi, Madras, Hyderabad, Bangalore, and Ahmedabad